Impacts of energy transition on Liquefied Natural Gas shipping: A case study of China and its strategies. (January 2022) - Yin, Yuwei; Lam, Jasmine Siu Lee
Abstract: Energy transition has been a global trend for decades, but very little literature can be found on how energy shipping is affected. Particularly, the coal-to-gas transition of China has intensified the nation's reliance on Liquefied Natural Gas (LNG) shipping import, especially through a strategic maritime link, the Straits of Malacca and Singapore (SOMS). If the SOMS is blocked in conflicts or incidents, energy supplies of China will be disrupted. Driven by practical significance and the literature gap, a case study of China is formulated to investigate how shocks in natural gas supply and demand will impact LNG shipping import volumes of China and its reliance on the SOMS, especially in the context of energy transition and the Belt and Road Initiative (BRI). An innovative System Dynamics model is developed to simulate natural gas supply and demand of China based on historical data, policies, and market information (i.e. energy prices, BRI projects and LNG contracts). It is recommended for China to create financial incentives to support renewable energy and shale gas development, enhance natural gas pipeline utilization and encourage overseas LNG infrastructure investments. BRI members are recommended to diversify export routes, expanding shares in global pipeline natural gas and LNG markets.